Interface laws for impregnated diamond tools for a given state of wear. (January 2015) - Franca, L.F.P.; Mostofi, M.; Richard, T.
Abstract: Impregnated diamond bit has emerged as one of the most commonly used types in the extraction of underground resources in hard and abrasive formations. Despite the success and its frequent use, the drilling performance of these bits is still quite volatile and inconsistent due to a lack of fundamental understanding of the mechanisms governing the bit/rock interface. Impregnated diamond bits are rotary drag bits, in which the cutters also called segments or crowns are comprised of sintered metal powder with diamonds (natural or synthetic) uniformly distributed throughout its volume. The diamonds, which are exposed at the bit surface, are responsible for cutting away rock while the matrix provides the necessary bonds to retain the diamonds during their cutting life. Focusing our attention to evaluate performance of impregnated diamond bit, it is absolutely essential to establish interface laws, and also to establish a distinction between "topologically-invariant" and "topologically-variant" responses. Initially, specific laboratory tests are conduced with single segments and a procedure to identify topologically-invariant cutting response proposed. Interface laws for a segment are then derived, assuming that the cutting response is composed of two independent processes, pure cutting process and frictional contact or rubbing; and the rubbing process is composed by losses generated at both contact surfaces: diamond wear flat areas and matrix bearing surface. Next, impregnated diamond bit responses are investigated and the interface laws obtained, using the same logic established for segments. Finally, the parameters of the model are identified through an extensive series of laboratory tests. Abstract : Highlights: A new model for impregnate diamond segments and bits is proposed. The energy dissipation at the tool/rock interface can be considered as a combination of two independent processes: pure cutting process and frictional contact or rubbing process. A series experimental test is performed to identify a signature of the drilling/cutting response and the model parameters.